Does competition matter in measures of job accessibility? Explaining employment in Los Angeles. (October 2017) - Merlin, Louis A.; Hu, Lingqian
Abstract: Planning organizations are increasingly looking to accessibility measures to understand how well the transportation system provides access to employment opportunities. However, the most common type of job accessibility measure employed in planning practice, the cumulative opportunity measure, considers job supply but overlooks competition for jobs. Therefore, the cumulative opportunity measure may not fully capture workers' access to job opportunity. In this paper, we examine four accessibility measures, two of which account for spatial competition and the other two do not, using the Los Angeles metropolitan area as a case study. We find that measures of competitive accessibility have stronger associations with employment than non-competitive accessibility measures. We examine the relationship between residential accessibility and employment for four separate levels of educational attainment, and we find that competitive measures are especially pertinent for population segments with lower educational attainment. Therefore, we recommend competitive accessibility measures to assess the employment opportunity more accurately.